Latent profile analysis of empathy ability and its relationship with professional quality of life among hospice nurses in China - Yaling Wang; Chuntao Wang; Ziwei Yang; Yuezhong Tang; Wen Chen; Yawen Zheng; Zhiming Wei; Huiling Li (BMC, 2024)
Abstract Background Empathy is important in hospice nursing clinics and may influence nurses' professional quality of life (ProQOL). However, present studies ignoring each empathic dimension, and few researches have explored the correlation between empathy and ProQOL in hospice nurses in Asia. To better understand hospice nurses' empathy abilities in China and its relationship with ProQOL, the aim of this study was to identify the latent profiles and its influencing factors of hospice nurses' empathy ability, as well as differences in ProQOL across each latent profile. Methods A cross-sectional study was conducted from October 2021 to September 2022, and a total of 725 hospice nurses were recruited from different geographic regions in China. Participants completed the Empathy Ability Scale for Hospice Nurses and the Brief Professional Quality of Life Scale. Latent profile analysis (LPA) was employed to identify latent profiles of empathy ability among hospice nurses in China. The predictors of hospice nurses' empathy ability in different latent profiles were assessed using multinomial logistic regression analysis. One-way ANOVA test and the Kruskal-Wallis test were used to compare the ProQOL scores in each latent profile of nurses' empathy ability. Results This study identified three latent profiles of hospice nurses' empathy ability, and those profiles labelled "poor empathy ability-high surface empathy expression" (n = 216, 29.8%), "moderate empathy ability" (n = 359, 49.5%) and "high empathy ability-high deep empathy expression" (n = 150, 20.7%). Multinomial logistic regression analysis suggested that age, hospital level, whether income meets expectations, interests in hospice care work, hospice work experience, and receiving psychological counselling were predictors of hospice nurses' profile membership of empathy ability. The scores of compassion satisfaction (CS) and burnout (BO) in ProQOL were significantly different across each profile (P < 0.001), while scores of secondary traumatic stress (STS) in ProQOL were not different across each profile (P = 0.294). Conclusions Hospice nurses' empathy ability was divided into three latent profiles, and enhancing empathy ability may be conducive to improving hospice nurses' CS, while reducing BO, thus fostering their overall quality of life. Nursing managers should identify hospice nurses at higher risk of BO and implement targeted interventions focused on enhancing nurse's empathy abilities.